Lead-free low-dimensional tetraalkylammonium manganese- and copper-based hybrid organic–inorganic perovskites for visual fluorometric Pb2+ ion detection - Kour, Prachi; Sahu, Pragati; Dambhare, Neha V.; Rath, Arup Kumar; Mukherjee, Shatabdi Porel (ACS Applied Optical Materials, 2024)
For the first time, we have synthesized lead (Pb)-free manganese (Mn)- and copper (Cu)-based hybrid organic–inorganic perovskite (HOIP) compounds, compound 1, (TEA)2MnBr4, compound 2, (TBA)2MnBr4, compound 3, (TEA)2CuBr4, and compound 4, (TBA)CuBr2 (where TEA is tetraethylammonium and TBA is tetrabutylammonium), under ambient conditions via mechanochemical synthesis methodology using a Kakuhunter-made planetary mixer. The compounds are characterized as 2D except for (TBA)CuBr2, which has crystallized in the 0D lattice. The synthesized compounds are phase pure and show a stable solid-state emission at room temperature. The Mn-based perovskite compound 1 showed excellent environmental photostability for over a month and reasonable stability under a relative humidity of 70–80%. The nanoparticle (NP) dispersions of compounds 1 and 2 were used further for fluorescence titration studies using various heavy metal cations, including transition metals and lanthanides (e.g., Y3+, Nb3+, Co2+, Ni2+, Ag+, Zn2+, Cd2+, Pb2+, Gd3+, and Dy3+), where they showed good fluorescence switching by the Pb2+ ion. Compound 1 demonstrated excellent fluorescence switching performance with Pb2+ titration with a Pb2+ detection limit of 2.43 × 10–8 M and hence can be used to fabricate a Pb2+ calorimetric sensor. A preliminary visual thin film-based sensor using NPs of compound 1 was fabricated to test the change in emission from blue to green in correlation with the results obtained in the NP solution during Pb2+ ion sensing. A fascinating in situ ion-exchange-based mechanism for the sensitivity of NPs of compound 1 is confirmed. This study reveals the ability of Pb-free Mn-based HOIPs to detect an oxidizing metal cation, Pb2+, efficiently and quantitatively.